Perancangan Aplikasi Pembelajaran Mengenal Huruf Alfabet Untuk Anak Usia Dini Berbasis Android - Liza Fitriana; Fadhilah Zuhdiyyah Lubis (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2025)
Early childhood education is a fundamental stage in a child's cognitive, social, emotional, and physical development. Recognition of the alphabet forms an important foundation for reading and writing skills. This study aims to design and develop an interactive and child-friendly Android-based alphabet learning application. The research method includes literature review and observation in early childhood education settings to identify user needs. The application is designed with multimedia elements such as images, sounds, animations, and educational quizzes, complete with a simple interface, bright colors, and intuitive navigation. Test results show that the application runs stably on various Android devices, has a fast response, and increases children's learning motivation through visual and audio interactions. This application is considered effective as an alternative learning medium that supports the alphabet recognition process, both at home and in formal education settings